Let
A = ∫ 1 2 x + a 2 x − a d x
Submit ⌊ 1 0 0 0 0 A ⌋ for a = 1 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Hi Alice Smith (it seems I cant mention you for some reason), could you organise the integration grandmaster series into a note? Because that way I can add it into my collection series RadMaths and it will be easier to keep track :)
The integral is Taking x − 1 = t 2 ∫ 1 2 x + x − 1 d x = ∫ 0 1 2 t t 2 + t + 1 d t = ∫ 0 1 ( 2 t + 1 ) t 2 + t + 1 − ∫ 0 1 t 2 + t + 1 = [ 3 2 ( t 2 + t + 1 ) 2 3 − 4 2 t + 1 t 2 + t + 1 − 8 3 sinh − 1 ( 3 2 t + 1 ) ] 0 1 = 2 3 − 3 1 − 4 3 3 − 1 − 8 3 ( sinh − 1 ( 3 ) − sinh − 1 ( 3 1 ) ) = 1 . 4 6 0 5 Answer is [ 1 0 0 0 0 × 1 . 4 6 0 5 ] = 1 4 6 0 5 Note
∫ t 2 + t + 1 d t = 4 2 t + 1 t 2 + t + 1 + 8 3 sinh − 1 ( 3 2 t + 1 )
Where is d t in the first line 3 r d integral and 4 t h
A = = = = = ≈ ∫ 1 2 x + x − 1 d x Let u = x − 1 2 ∫ 0 1 u ( u + 2 1 ) 2 + 4 3 d u Let t = u + 2 1 2 ∫ 2 1 2 3 t t 2 + 4 3 d t − ∫ 2 1 2 3 t 2 + 4 3 d t Let t = 4 3 tan θ 3 2 ( t 2 + 4 3 ) ∣ ∣ ∣ ∣ 2 1 2 3 − 4 3 ∫ 3 π 6 π sec 3 θ d θ 3 2 ( t 2 + 4 3 ) ∣ ∣ ∣ ∣ 2 1 2 3 − 4 3 ( 2 1 sec θ tan θ + 2 1 ln ∣ sec θ + tan θ ∣ ) ∣ ∣ ∣ ∣ 3 π 6 π ∫ sec 3 x d x = 2 1 ( sec x tan x + ln ∣ sec x + tan x ∣ ) + C 1 . 4 6 0 5 2 7 4 …
Suppose that 0 < a < 2 3 2 . If we put u = x − a + 2 1 a 2 , then u 2 + 4 1 a ( 4 − a 3 ) = x + a 2 x − a d u d x = 2 u − a 2 and hence A ( a ) = ∫ 1 2 x + a 2 x − a d x = ∫ u ( 1 ) u ( 2 ) u 2 + 4 1 a ( 4 − a 3 ) ( 2 u − a 2 ) d u = [ 3 2 ( u 2 + 4 1 a ( 4 − a 3 ) ) 2 3 ] u ( 1 ) u ( 2 ) − a 2 ∫ 1 2 u 2 + 4 1 a ( 4 − a 3 ) d u = [ 3 2 ( u 2 + 4 1 a ( 4 − a 3 ) ) 2 3 ] u ( 1 ) u ( 2 ) − 4 1 a 3 ( 4 − a 3 ) ∫ v ( 1 ) v ( 2 ) cosh 2 v d v = [ 3 2 ( u 2 + 4 1 a ( 4 − a 3 ) ) 2 3 ] u ( 1 ) u ( 2 ) − 8 1 a 3 ( 4 − a 3 ) ∫ v ( 1 ) v ( 2 ) ( cosh 2 v + 1 ) d v = [ 3 2 ( u 2 + 4 1 a ( 4 − a 3 ) ) 2 3 ] u ( 1 ) u ( 2 ) − 8 1 a 3 ( 4 − a 3 ) [ sinh v cosh v + v ] v ( 1 ) v ( 2 ) = [ 3 2 ( u 2 + 4 1 a ( 4 − a 3 ) ) 2 3 − 2 1 a 2 u ( u 2 + 4 1 a ( 4 − a 3 ) ) 2 1 ] u ( 1 ) u ( 2 ) − 8 1 a 3 ( 4 − a 3 ) [ v ] v ( 1 ) v ( 2 ) = [ 3 2 ( x + a 2 x − a ) 2 3 − 2 1 a 2 ( x − a + 2 1 a 2 ) x + a 2 x − a ] 1 2 − 8 1 a 3 ( 4 − a 3 ) [ sinh − 1 ( a ( 4 − a 3 ) 2 u ) ] u ( 1 ) u ( 2 ) In particular A ( 1 ) = [ 3 2 ( x + x − 1 ) 2 3 − 2 1 ( x − 1 + 2 1 ) x + x − 1 ] 1 2 − 8 3 [ sinh − 1 ( 3 2 u ) ] 2 1 2 3 = 4 5 3 − 1 2 5 − 8 3 sin − 1 3 + 8 3 sinh − 1 ( 3 1 ) and so ⌊ 1 0 0 0 0 A ( 1 ) ⌋ = 1 4 6 0 5 .
Problem Loading...
Note Loading...
Set Loading...
A = ∫ 1 2 x + x − 1 d x = 2 ∫ 0 1 u u 2 + u + 1 d u = 2 ∫ 0 1 u ( u + 2 1 ) 2 + 4 3 d u = 2 ∫ sinh − 1 3 1 sinh − 1 3 ( 2 3 sinh t − 2 1 ) ⋅ 4 3 cosh 2 t d t = 4 3 3 ∫ sinh − 1 3 1 sinh − 1 3 cosh 2 t sinh t d t − 4 3 ∫ sinh − 1 3 1 sinh − 1 3 cosh 2 t d t = 4 3 3 ∫ 3 2 2 v 2 d v − 8 3 ∫ sinh − 1 3 1 sinh − 1 3 ( cosh 2 t + 1 ) d t = [ 4 3 v 3 ] 3 2 2 − [ 1 6 3 sinh 2 t + 8 3 t ] sinh − 1 3 1 sinh − 1 3 = 2 3 − 3 2 − 4 3 3 + 4 1 − 8 3 sinh − 1 3 + 1 6 3 ln 3 = 4 8 6 0 3 − 2 0 + 9 ln 3 − 1 8 sinh − 1 3 ≈ 1 . 4 6 0 5 2 7 4 3 Let u 2 = x = 1 ⟹ 2 u d u = d x Let u + 2 1 = 2 3 sinh t ⟹ d u = 2 3 cosh t d t Let v = cosh t ⟹ d v = sinh t d t
Therefore ⌊ 1 0 0 0 0 A ⌋ = 1 4 6 0 5 .